AN ANALYSIS SEMANTIC OF AL-QUR’AN IN LEXICAL MEANING ON SURAH AL-BAYYINAH - Yuliawati, Fitrah; Woni, Abdul (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2022)
Abstract Semantic learns about meaning of word, phrase and sentence. Lexical is a form of semantic that study about meaning of word and meaning relationships among word or phrase. This research is aimed to identify the lexical meaning and types of lexical meaning found in Surah Al-Bayyinah. Surah Al-Bayyinah is 98th surah on Al- Qur’an, which consists of eight verses.. The design of this research by the form of qualitative method since the researcher conducts the analysis on Surah Al-Bayyinah. In this research, the researcher uses Lyon’s theory to analyze semantics in lexical meaning on surah Al-Bayyinah. The result of this research show there are three types of lexical meaning found on surah Al-Bayyinah consist of synonym with eighteen words in 7 verses, connotative with four words or phrases in 4 verses and denotative with four words or phrases in 4 verses.Researcher suggest the reader and the next researcher who interest to make this research as reference, the reader and the next researcher can conduct other style of lexical meaning on Al-Qur’an or song with other branch of linguistic. Researcher hope this research will be useful by the reader and the next researcher. Keywords: Semantic, Lexical, Surah Al-Bayyinah